Sintering effect on mechanical properties of composites of bovine hydroxyapatite (BHA) and Li2O - OKTAR, FAİK NÜZHET; PEKER, İSMAİL; GÜNDÜZ, OĞUZHAN; SALMAN, SERDAR; GENÇ, YUNUS EMRE (Trans Tech Publications Ltd, 2006)
In this study, hydroxyapatite (HA) material, obtained from calcinated bovine bone (BHA), was mixed with 0.25, 0.50, 1.00, and 2.00 wt% Li 2CO3. The pressed pellets were sintered at various sintering temperatures between 900°C and 1300°C. Measurements of compression strength, microhardness, and density, along with SEM observation and X-ray diffraction analysis were performed. The experimental results showed that the samples with 0.25 and 0.50% Li2CO3. reached a maximum of densification and the highest values of compression strength and microhardness were achieved after sintering at 1300°C. The wetting effect of a Li2O-associated glassy phase was observed even from 900°C.
Keywords: Bovine Derived Hydroxyapatite; Lithium Oxide; Mechanical Properties; Sintering